2016
DOI: 10.1038/ncomms11686
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise phosphorylation of p65 promotes NF-κB activation and NK cell responses during target cell recognition

Abstract: NF-κB is a key transcription factor that dictates the outcome of diverse immune responses. How NF-κB is regulated by multiple activating receptors that are engaged during natural killer (NK)-target cell contact remains undefined. Here we show that sole engagement of NKG2D, 2B4 or DNAM-1 is insufficient for NF-κB activation. Rather, cooperation between these receptors is required at the level of Vav1 for synergistic NF-κB activation. Vav1-dependent synergistic signalling requires a separate PI3K-Akt signal, pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
138
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 125 publications
(157 citation statements)
references
References 53 publications
13
138
0
Order By: Relevance
“…DKK3 is a suppressor in cancer cells, however, we found that DKK3 suppressed the cytotoxicity of NK cells in this study. Erk signaling pathway activation was crucial to cytotoxic degranulation of NK cells . Both in this study and other previous studies, it has been reported that DKK3 inhibited the activation of the Erk pathway in cells .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…DKK3 is a suppressor in cancer cells, however, we found that DKK3 suppressed the cytotoxicity of NK cells in this study. Erk signaling pathway activation was crucial to cytotoxic degranulation of NK cells . Both in this study and other previous studies, it has been reported that DKK3 inhibited the activation of the Erk pathway in cells .…”
Section: Discussionsupporting
confidence: 78%
“…Erk signaling pathway activation was crucial to cytotoxic degranulation of NK cells. 27 Both in this study and other previous studies, it has been reported that DKK3 inhibited the activation of the Erk pathway in cells. 28,29 In addition, we found that DKK3 could bind NKG2D and the DKK3-NKG2D complex is difficult to form immunological synapses (IS).…”
Section: Discussionsupporting
confidence: 68%
“…Using an activation model that combines 2B4 with NKG2D or DNAM-1, we found that SLP-76-Vav1 and NF-κB p65 function as common checkpoints for multiple activation pathways in NK cells (Figure 1). 40, 41 In addition, we recently provided evidence demonstrating E3 ubiquitin ligase c-Cbl and glycogen synthase kinase (GSK)-3β as negative regulators of NK cell activation triggered by multiple activating receptors (Figure 1). 25, 42 Because cancer cells express various and heterogeneous ligands for NK activating receptors, it would be desirable to target and modulate signaling molecules that are common to multiple activating receptors for NK cell activation.…”
Section: Common Signaling Checkpoints For Nk Cell Activationmentioning
confidence: 99%
“…Rather, their synergistic combination is required for effective NF-κB activation and NK cell responses. 41 This combination relays independent and complementary signals that result in the combined phosphorylation of the ‘upstream' SLP-76-Vav1 and unexpectedly, the ‘downstream' NF-κB p65 subunit. Vav1-dependent synergistic signals are required for p65 phosphorylation and NF-κB activation, which is supported by the stepwise regulation of Vav1 and p65 phosphorylation in NK cells.…”
Section: Common Signaling Checkpoints For Nk Cell Activationmentioning
confidence: 99%
See 1 more Smart Citation